2023
DOI: 10.2196/45502
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Frailty and the Increased Risk of Adverse Outcomes Among 38,950 UK Biobank Participants With Prediabetes: Prospective Cohort Study

Abstract: Background Compared with adults with normal glucose metabolism, those with prediabetes tend to be frail. However, it remains poorly understood whether frailty could identify adults who are most at risk of adverse outcomes related to prediabetes. Objective We aimed to systematically evaluate the associations between frailty, a simple health indicator, and risks of multiple adverse outcomes including incident type 2 diabetes mellitus (T2DM), diabetes-rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the absence of objective mobility measures such as gait speed in the UK Biobank dataset led us to rely on self‐reported walking pace as a proxy indicator of mobility. 32 Nevertheless, it is important to acknowledge that the absence of such objective mobility measures may impact the accuracy and quantification of frailty assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the absence of objective mobility measures such as gait speed in the UK Biobank dataset led us to rely on self‐reported walking pace as a proxy indicator of mobility. 32 Nevertheless, it is important to acknowledge that the absence of such objective mobility measures may impact the accuracy and quantification of frailty assessments.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The frailty phenotype encompasses five traits: weight loss, exhaustion, low physical activity, slow walking speed and low grip strength. 31 To adapt the data for use in the UK Biobank, we referred to previous reports and made slight adjustments to the criteria, 32 as outlined in Table S1 . Frailty status was evaluated based on the sum of scores for all five frailty items, with a higher total score indicating a higher frailty level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is characterized by decreased functioning of multiple physiological systems, which increases the risk of adverse health outcomes and can occur at all ages ( 29 , 44 ). Previous study on frailty and diabetes based on two prospective cohorts suggested that frailty was the predisposing factor for diabetes and increases its risk of death ( 11 , 18 ). At present, there is a lack of studies on frailty and GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Older adult T2DM patients with depression have significantly elevated levels of C-reactive protein, interleukin-6 and tumor cytokines, which also contribute to frailty ( 56 , 57 ). Meanwhile, older adult T2DM patients with depression are significantly less sociable and active and are more likely to have a sedentary lifestyle ( 58 ), which further contributes to muscle wasting. And muscle wasting and reduced muscle strength are important markers of frailty ( 59 ).…”
Section: Discussionmentioning
confidence: 99%